Digital Image Watermarking (DIW) Menggunakan Wavelet Transform Domain - Yoiceta Vanda; Setyawan Ary Cahyono (Politeknosains, 2016)
Digital Image has its advantages can be duplicated easily. Need to add information embedded on digital image as a mark of Multimedia Intellectual Property Rights. Technology to embedded mark into images called Digital Image Watermarking (DIW). This research aimed to : created software Digital Image Watermarking (DIW) in Wavelet Transform Domain, that can be applied by the public. The methods for this research are :1. Study Literature, 2. Sampling method, distributed some questionnaire to public, and then from the result, we can take the sample for preliminary data, so the conclusion about Digital Image Watermarking (DIW) can be obtained, 3. create the Digital Image Watermarking (DIW) software. DIW given an attack geometric transformation: scaling, cropping, translation, rotation, compression, and median filter. The result of this research is Digital Image Watermarking (DIW) in the wavelet transform domain, with spread spectrum mark robust to geometric transformation: scaling, cropping, translation, rotation, compression, and median filter. The conclusion is Digital Image Watermarking (DIW) in the Wavelet Transform Domain as the technology of Multimedia Intellectual Property Rights robust to geometric transformation.